Linguagem e redes sociais: o facebook como espaço de aprendizagem da língua portuguesa para alunos surdos - Tomé Júnior, Erivan Lopes (2014)
The internet is now one of the media more accessible messages and thereby spread their language and became globalized. In this context, too, is part of Facebook, a social network that can provide deaf students the opportunity to present their ideas, conduct online discussions and collaborate effectively for learning the Portuguese language teaching from the use of contemporary digital technologies. Thus, this research aims to contribute to scale some aspects of the dynamics of inclusion of deaf students, through the use of Facebook. Using this social network, is presented as one of the possibilities that can contribute digital literacy and more specifically, the practice of reading and writing audience on screen. The specific objective is to present these mechanisms as an ally of educators in diverse classrooms that country. The research falls within the ethnographic process, based on the descriptive and exploratory model, since after the experiment, we used such methods for organizing and interpreting the results, analyzing the use of Facebook, with the effective participation of deaf students and teacher researcher. During the shares postings, publications and interactions occurring with other users were observed. Given all this, it can be stated that the interaction established through Facebook shortens distances, transposing barriers and ushers in a completely novel way of establishing communication between netizens in cyberspace. During the research it was realized that the Face has established a new way to communicate online. Thereby confirming its role as a disseminator of multiple and diverse knowledge.